A new configuration of patch antenna array for rectenna array applications - A. Taybi; A. Tajmouati; J. Zbitou; L. El Abdellaoui; M. Latrach; A. Errkik (Universitas Ahmad Dahlan, 2019)
The performance and advantages of microstrip patch antennas made them a field of interest for wireless power transmission applications, especially for rectenna systems where the choice of the antenna is a crucial step. In this paper, a 5.8 GHz circularly polarized patch antenna has been designed and fabricated, then mounted by using 4 elements to achieve an antenna array to enhance the captured power to be converted by the rectifier circuit. The antenna array is well matched at 5.8 GHz in terms of reflection coefficient and has a directivity of 11dB and a gain of 6 dB. Results have been confirmed by fabrication.